5th International Conference on Computer Sciences and Convergence Information Technology 2010
DOI: 10.1109/iccit.2010.5711189
|View full text |Cite
|
Sign up to set email alerts
|

Information gain and adaptive neuro-fuzzy inference system for breast cancer diagnoses

Abstract: Abstract-This paper presents a new approach for breast cancer diagnosis using a combination of an Adaptive Network based Fuzzy Inference System (ANFIS) and the Information Gain method. In this approach, the ANFIS is to build an input-output mapping using both human knowledge and machine learning ability and the information gain method is to reduce the number of input features to ANFIS. An experimental result shows 98.23% accuracy which underlines the capability of the proposed algorithm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In an evaluation on a BC dataset, they found that their technique was 97.38% accurate using 10-fold cross-validation. The adaptive neuro-fuzzy inference system (ANFIS) and information gain (IG) were used as a feature selection strategy by Ashraf et al [21] to develop a BC diagnosis model. Here, IG is applied to reduce the number of features to the optimal number, and then the dataset is passed to the ANFIS classifier.…”
Section: Related Workmentioning
confidence: 99%
“…In an evaluation on a BC dataset, they found that their technique was 97.38% accurate using 10-fold cross-validation. The adaptive neuro-fuzzy inference system (ANFIS) and information gain (IG) were used as a feature selection strategy by Ashraf et al [21] to develop a BC diagnosis model. Here, IG is applied to reduce the number of features to the optimal number, and then the dataset is passed to the ANFIS classifier.…”
Section: Related Workmentioning
confidence: 99%
“…Technique Classification rate (%) [3] IGANFIS 98.24 [32] SANFIS 96.07 [10] L.V .Q 95,82 [15] Fuzzy 96,71 [21] Fuzzy-GA1 97,36 We can say that neuro-fuzzy systems are connectionist models that allow learning as artificial neural network , but their structure can be interpreted as a set of fuzzy rules .Fuzzy logic and neural networks form the basis of the majority aided diagnostic intelligent systems.It would be interesting to combine the two approaches to exploit both advantages.…”
Section: Referencesmentioning
confidence: 99%
“…Our goal is to obtain a high performance with a reasonable number of rules. In this study, we have used information gain algorithm [3] in order to reduce the feature number of the Wisconsin breast cancer database (WBCD), So we obtain 6 features instead of 9. Table 6 shows some results obtained for our experimentation: Initial parameters of membership functions are shown in the following figure 3:…”
Section: Choice Of Parametersmentioning
confidence: 99%
“…The lung cores (valleys) including pixels with gray levels less than GL [ 1 ] then should be in Region [ 0 ] (Fig. 3b).…”
Section: Lung Boundary Detection Algorithmmentioning
confidence: 99%
“…The experimental result obtained with an algorithm to detect early nodules for lung cancer and TP is very encouraging. Data mining and other artificial intelligent techniques may be used to make the system becoming an active and powerful expert system [1].…”
Section: E Other Cxr Analysismentioning
confidence: 99%